(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
In August 1911, Leonardo da Vinci!s most famous painting was stolen. The repercussions of the case in the written press made the painting omnipresent for people who till then knew very little about it, giving it from that moment on the status of an authentic myth and art icon, a role that it had begun to assume in the middle of the nineteenth century. As happened in other places, the Spanish press spread the news of the event, bringing it, the painting, and its history closer to the Spanish people of the beginning of the twentieth century. At the same time, mass media outlets like the press, advertising, and cinema made use of the art work as a selling point, taking advantage of its popularity.